Análisis y evaluación de la cartera de crédito en la cooperativa de ahorro y crédito de la pequeña empresa Cacpe – Loja sucursal Vilcabamba periodo 2019 - 2020. - Jaramillo Cajamarca, Yulissa Elizabeth (2022)
The present research of curricular integration is entitled "ANALYSIS AND EVALUATION OF THE CREDIT PORTFOLIO IN THE COOPERATIVA DE AHORRO y CREDITO DE LA PEQUEÑA EMPRESA CACPE- LOJA -BRANCH BANK VILCABAMBA PERIOD 2019-2020, was developed in order to know the situation of the credit portfolio and its recovery management. An analytical, descriptive, and explanatory study of all the portfolios that make up the credit portfolio of CACPE-LOJA bank branch-Vilcabamba was used for its analysis and evaluation, followed by a vertical and horizontal analysis by portfolio, then it was represented graphically for a better understanding, allowing us to determine the degree of loan placements and default rate of them. Subsequently, it was verified that the loan portfolio with the highest placement is the priority consumer portfolio, with 74.64%. of credits collecting which is directed to individuals for the purchase of goods, services, or expenses not related to a productive activity, by means of a Comparative analysis It was possible to determine that the microcredit portfolio increased significantly from one period to another at 174.97% representing a value of $ 542,295.34, the noninterest bearing priority consumer portfolio at 63.35% representing $ 21,578.90 and portfolio that does not accrue interest with 63.35%, equivalent to $ 21,578.90, and finally with 40.81% of financial provisions. Following the implementation of delinquency indicators in the credit portfolio, it was determined that the delinquency rate remained at 2.20% in 2019 with a value of $90,964.93 and a balance of $93,860.03 in 2020.which means that the COOPERATIVA DE AHORRO Y CREDITO CACPE-branch bank Vilcabamba has not been able to recover the values of the written-off portfolio due to the financial crisis that the country is going through up to the present time because of COVID-19. Finally, the conclusions and the indicators are presented based on the development of the research according to the interview made to the manager of the COOPERATIVA DE AHORRO Y CREDITO CACPE-LOJA, bank branch Vilcabamba, and in reference to this, the respective recommendations are also elaborated, which contribute to the decision-making process.